Correlations between psychological anxiety symptoms and physical anxiety symptoms in dental anxiety—a cross-sectional study with 1327 patients - Magerfleisch, Laura Agnes Ingrid; Cunoti, Nertsa; Qorri, Rezart; Weil, Katharina Marilena; Tröger, Hannah; Häring, Juliane; Irmscher, Lisa; Petrowski, Katja; Berth, Hendrik (Frontiers in Oral Health, 2025)
BackgroundDental anxiety is a prevalent phenomenon with the potential to impact both psychological well-being and oral health outcomes. It may lead to individuals avoiding treatment. This study aims to explore the relationship between psychological anxiety symptoms and physical anxiety symptoms in dental anxiety.MethodsBetween 2019 and 2022, a cross-sectional study was conducted including 1,327 patients from a variety of dental practices in Germany and students (age range: 18–85 years; mean: 39.65 years, 60.7% female). Participants completed validated questionnaires, including the Dental Anxiety Scale (DAS), the Scale Somato-visceral arousal of the Dental Fear Survey (DFS-SVA), the Brief Symptom Inventory 18 (BSI-18 GSI), and the Oral Health Impact Profile (OHIP-5). Data was analysed using Mann–Whitney-U-tests, Spearman correlations, Kruskal–Wallis-tests and linear regression models. The significance level was set at p = 0.05.ResultsThe mean value for dental anxiety (DAS) was 9.81 (SD = 4.07) and for physical anxiety symptoms (DFS-SVA) 10.51 (SD = 4.70). Of the participants, 808 (60.9%) reported no dental anxiety, 368 (27.7%) were somewhat anxious and 151 (11.4%) reported severe dental anxiety. A strong correlation was observed between DAS and DFS (r = 0.544), while moderate correlations were found between DAS and BSI-18 (r = 0.300) and between DAS and OHIP-5 (r = 0.371). The application of regression analysis indicated that DFS-SVA was the strongest predictor of DAS scores (β = 0.434, p < 0.001), followed by BSI-18 GSI (β = 0.285, p < 0.001) and age (β = 0.174, p < 0.001). Gender was not found to have a significant influence on results. A significant disparity was observed in the results between male and female scores and on the DAS, DFS-SVA, and BSI-18 GSI compared to men.ConclusionThe study corroborates substantial correlation between psychological dental anxiety and physical anxiety symptoms. These findings underscore the necessity for early detection and targeted interventions within dental practices with the aim of enhancing both oral health and overall quality of life. It is recommended that future research endeavours focus on the investigation of causal relationships and the identification of effective treatment strategies to further enhance patient care.